Effects of soaking and grinding conditions on anti-nutrient and nutrient contents of soy milk (Journal of the Bangladesh Agricultural University, 2018)
Although soy milk is a very good source of nutrient with high biological value, the presence of anti-nutritional factors affects its nutrition quality and limits bioavailability of the nutrients. The effects of soaking duration and combination of soaking and grinding (hot or cold) on phytate, lipoxygenase, urease, trypsin inhibitor activity, protein solubility and other nutrient contents were investigated. Soaking alone at 55 and 60oC for different durations was found effective for the reduction of lipoxygense activity. Combination of soaking, blanching (80oC for 10 min) and hot grinding (100oC) significantly (P>0.05) reduced urease activity, more than 80% phytate activity and deactivated trypsin inhibitor, but did not affect protein solubility. Meanwhile, protein solubility (10–15%) was increased due to hot grinding. Soy milk extracted from soaking at 55 and 60oC for 2, 4 and 6 h with hot grinding provided higher protein content compared to cold grinding. Increase in soaking temperature from 55 to 60oC increased the extracted solid content having a potential fraction of lipid. Increasing soaking time from 4 to 6 h did not show any significant difference in terms of phytate inhibition, urease activity reduction, trypsin inhibition and protein solubility except lipoxygenase activity. The results suggested that soaking of soybean at 60oC for 6 h and hot grinding (100oC) with blanching at 80oC for 10 min is the best for reducing anti-nutrient and retaining nutrient activity for soy milk and other soy-based products.J. Bangladesh Agril. Univ. 16(1): 158-163, April 2018